Socio-Economic Requirements as a Fundament of Innovation in Food Packaging - Agnieszka Cholewa-Wójcik; Agnieszka Kawecka; Carlo Ingrao; Valentina Siracusa (Journal of Entrepreneurship, Management and Innovation)
The food packaging industry trends reflect the identified needs and requirements of consumers because entrepreneurs should satisfy changing consumer requirements to achieve and maintain a competitive advantage due to innovation. In the group of socio-economic needs, the most important ones are lifestyle changes, improving the quality of life through the added value offered to consumers through packaged products, profitable companies in the sector, packaged product safety and environmental protection. The main aim of the study was exploring the validity of food packaging requirements concerning the satisfaction of consumer needs. The resulting hierarchy of important needs and requirements represents the foundation for solutions and strategies to improve the quality of a consumer’s life. Analysis of the results clearly shows that among all socio-economic needs and requirements posed to food packaging, safety is the most critical need for consumers. Other packaging properties such as convenience and legal requirements fulfillment are important. Proposed model packaging, which will stratify consumers’ needs and requirements and will help to improve their quality of life, should be characterized by health, simplicity, identity, aesthetics, and meaning. The packaging industry is a branch considered to have high potential in the field of applying innovative solutions. This is mainly related to the desire of introducing solutions in the areas of improving safety, functionality, communication and environmental protection. Identification and understanding of consumer needs is a valuable source of information useful when developing improvements. Proposed components of model packaging follow the motto of the World Packaging Organization, which says: “Better quality of life through better packaging.”